Grape pomace as a natural source of antimicrobial agents for food preservation - Micaela Galante; María Emilia Brassesco; Carollyne Maragoni Santos; Carolina Beres; Ana Elizabeth Cavalcante Fai; Ana Elizabeth Cavalcante Fai; Ignacio Cabezudo (Frontiers in Nutrition, 2025)
Grape pomace, a by-product of winemaking, has emerged as a promising source of natural antimicrobial compounds for food applications. In response to increasing concerns regarding foodborne illnesses and consumer demand for clean-label products, its valorization represents a sustainable approach to enhance food safety and shelf life. This review combines a bibliometric analysis with a critical examination of the scientific literature. The bibliometric analysis identifies leading authors, institutions, countries, and research trends related to the use of grape pomace in food preservation. The literature review summarizes extraction techniques and antimicrobial evaluations. Grape pomace is rich in phenolic compounds with demonstrated antibacterial and antifungal activity. The antimicrobial effectiveness depends on factors such as grape variety, extraction method, polyphenol profile, and target microorganisms. Its incorporation into food productsincluding meat, dairy, and beverageshas shown promising results. Additionally, bioactive extracts have been applied in edible films, coatings, and active packaging to inhibit microbial growth and prolong shelf life. The evidence supports the potential of grape pomace as an effective antimicrobial food additive. However, challenges remain, including the need for standardized extraction protocols, deeper understanding of antimicrobial mechanisms, and comprehensive safety and efficacy evaluations in real food systems. Addressing these gaps is essential to facilitate the development of innovative food preservation strategies based on grape pomace bioactives.